L-Dunford-Pettis property in Banach spaces - Retbi, A.; El Wahbi, B. (Methods of Functional Analysis and Topology, 2016)
In this paper, we introduce and study the concept of L-Dunford-Pettis sets and L-Dunford-Pettis property in Banach spaces. Next, we give a characterization of the L-Dunford-Pettis property with respect to some well-known geometric properties of Banach spaces. Finally, some complementability of operators on Banach spaces with the L-Dunford-Pettis property are also investigated.